In vitro activity of a new carbapenem antibiotic, BO-2727, with potent antipseudomonal activity. - Nakagawa, S (1993)
BO-2727, a new 1-beta-methyl-carbapenem, was active at concentrations of 6.25 micrograms/ml or less against gram-positive and gram-negative bacteria, including some imipenem- and/or meropenem-resistant (MICs, > or = 12.5 micrograms/ml) Pseudomonas aeruginosa strains, against which it proved generally fourfold more active than imipenem and meropenem. BO-2727's antipseudomonal activity and its broad spectrum merit further investigation for clinical use by itself, since it was stable in the presence of renal dehydropeptidase I.